A quantum convolution autoencoder for handwritten letters and digits: A case study - Sawerwain, Marek; Kowal, Marek; Korbicz, Józef (1951- ) (Zielona Góra: Uniwersytet Zielonogórski)
The concept of an autoencoder is a key element of modern machine learning methods. It is used, e.g., to compress the input data into a lower-dimensional representation, which is later employed in other machine learning algorithms. In the area of quantum computing application methods, quantum machine learning is also developing dynamically, with the concept of a quantum autoencoder also present.
Keywords: autoencoders; quantum autoencoder; convolution quantum circuit